2019
DOI: 10.2147/pgpm.s187657
|View full text |Cite
|
Sign up to set email alerts
|

<p>Population&rsquo;s perspectives toward biobanks in scientific research: a study from Jordan</p>

Abstract: BackgroundBiobanks (biorepositories) were established to compile collected bio-specimens for future research and usage. The collection/storage of bio-specimens triggers several social, legal, and ethical implications where public attitudes can represent the core measurement/parameter in defining the most acceptable practices and ethical approaches when dealing with biobanks.AimThe aim of this study was to explore and understand population’s perspectives, expectations, and concerns toward biobanks in Jordan.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 33 publications
4
44
4
Order By: Relevance
“…Regarding biobanks attitude of the study participants, only 47.1% of the paramedical and 52.2% of the administrative team agreed to provide vital sample to help in the diagnosis of diseases in a biobank; also, only 40% of the paramedical and 36.6% of the administrative teams agreed to help in the collection of samples for a biobank. This is in contrast to Alzoubi's study where there was overwhelming support (> 85%) for the establishment of biobanks in Jordan, and most of the participants agreed on the importance of biobanks and sample donation in promoting medical research [16]. Also, all of interviewees were willing to share their blood sample or donate it to biobank for future use in Sakulthaew et al's study, and in Igbe and Adebamowo's study, the majority of the participants were willing to participate in biobank research for non-communicable diseases [14,17].…”
Section: Discussioncontrasting
confidence: 80%
“…Regarding biobanks attitude of the study participants, only 47.1% of the paramedical and 52.2% of the administrative team agreed to provide vital sample to help in the diagnosis of diseases in a biobank; also, only 40% of the paramedical and 36.6% of the administrative teams agreed to help in the collection of samples for a biobank. This is in contrast to Alzoubi's study where there was overwhelming support (> 85%) for the establishment of biobanks in Jordan, and most of the participants agreed on the importance of biobanks and sample donation in promoting medical research [16]. Also, all of interviewees were willing to share their blood sample or donate it to biobank for future use in Sakulthaew et al's study, and in Igbe and Adebamowo's study, the majority of the participants were willing to participate in biobank research for non-communicable diseases [14,17].…”
Section: Discussioncontrasting
confidence: 80%
“…[3][4][5]8 Recent decades have witnessed a growing interest in conducting research involving human subjects in Jordan. 9,10 Informed consent, privacy, confidentiality, data storage and bio-specimen collection, and further analysis are some of ethical challenges of genetic studies in Jordan. [10][11][12][13] Despite numerous publications that address ethical issues related to informed consent in genetic studies, very little is known about consenting genetic studies in the Arab region.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Informed consent, privacy, confidentiality, data storage and bio-specimen collection, and further analysis are some of ethical challenges of genetic studies in Jordan. [10][11][12][13] Despite numerous publications that address ethical issues related to informed consent in genetic studies, very little is known about consenting genetic studies in the Arab region. 8,14 In this study, we aimed to assess the content of different ICFs from genetic studies conducted in Jordan to determine the degree of compliance according to essential requirements proposed by ICHGCP.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the extent of patients' privacy concerns in the research setting. For example, in a study involving Jordanian patients, nearly 40% cited the fear of a negative impact of research on privacy as a discouraging factor towards participating in biobanking research [45]. In an Egyptian study investigating Egyptian attitudes toward biobanking, 35.9% thought that samples and data might be used in a way that would breach privacy [32].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors cite trust as a central component of the research participant-researcher relationship [48,49]. In a Jordanian study investigating the public views toward biobanking research, a belief in trust affected a willingness to participation positively [45]. In a large survey in the US, willingness to participate in a biobank was lower in individuals who reported lower levels of trust in the healthcare system and their researchers [46].…”
Section: Discussionmentioning
confidence: 99%